2016
DOI: 10.5430/jnep.v6n8p1
|View full text |Cite
|
Sign up to set email alerts
|

Promoting empathy through immersive learning

Abstract: Objective: This paper reports on a mixed methods study to explore the use of immersive learning with a convenience sample of healthcare students (seven of Mental Health Nursing and twelve of Occupational therapy) in promoting empathy. Two immersive learning scenarios were created using real life stories of the symptoms experienced by people with psychosis and sufferers of Post Traumatic Stress Disorder (PTSD). Methods: Data were collected using a mixed methods approach: quantatively, using a pre and post test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Sweeney and Baker [31] and Berliner and Masterson [32] discuss the importance of empathy in patient-centered care and suggest that video-based teaching is educational interventions and mentioned that, when these occur at early childhood, they can be especially effective. Roberts et al [33] found that immersive learning scenarios can enhance empathy in healthcare students. Crandall and Marion [34] emphasizes the importance of identifying attitudes towards empathy and suggests that empathy can be taught and assessed as a cognitive skill.…”
Section: Methods To Measure Empathymentioning
confidence: 99%
“…Sweeney and Baker [31] and Berliner and Masterson [32] discuss the importance of empathy in patient-centered care and suggest that video-based teaching is educational interventions and mentioned that, when these occur at early childhood, they can be especially effective. Roberts et al [33] found that immersive learning scenarios can enhance empathy in healthcare students. Crandall and Marion [34] emphasizes the importance of identifying attitudes towards empathy and suggests that empathy can be taught and assessed as a cognitive skill.…”
Section: Methods To Measure Empathymentioning
confidence: 99%
“…Ervaringsleren lijkt een relevante manier om dit dieper leren te stimuleren. Zo toont onderzoek onder zorgprofessionals (in opleiding) aan dat het ervaren van een rolwisseling als cliënt bijdraagt aan persoonlijke reflectie, ethische reflectie en empathisch vermogen [13][14][15]. Ervaringsleren wordt in verband gebracht met de morele vorming van zorgprofessionals en is voor zorgprofessionals een aansprekende leerstrategie gebleken [16,17].…”
Section: Inleidingunclassified
“…Clinical simulation, particularly digital-technology-aided simulation, is becoming increasingly important in nurse education providing the potential for learners to take on both the role of the nurse or the patient 24 and may provide a useful mechanism to investigate how students learn to recognise odours associated with wound infection. Early tentative results suggest that simulation can be effective in promoting empathy 26 . It is anticipated that through preparation of students for the real world of malodorous wounds there will be an earlier identification of infection, patients quality of life will be enhanced, as students will be prepared to manage odours and the potential disgust associated with malodorous wound will be reduced.…”
Section: Wound Odourmentioning
confidence: 99%